Selling Sex in the City A Global History of Prostitution, 1600s-2000s (Volume 31) - Heerma van Voss, Lex; van Nederveen Meerkerk, Elise; Rodríguez García, Magaly (Brill, 2017)
Selling Sex in the City offers a worldwide analysis of prostitution that takes a long historical approach which covers a time period from 1600 to the 2000s. The overviews in this volume examine sex work in more than twenty notorious "sin cities" around the world, ranging from Sydney to Singapore and from Casablanca to Chicago. Situated within a comparative framework of local developments, the book takes up themes such as labour relations, coercion, agency, gender, and living and working conditions. Selling Sex in the City thus reveals how prostitution and societal reactions to the trade have been influenced by colonization, industrialization, urbanization, the rise of nation states, imperialism, and war, as well as by revolutions in politics, transport, and communication. Contributors are: Pascale Absi, Dlila Amir, Deborah Bernstein, Francesca Biancani, Thaddeus Gregory Blanchette, Amalia L. Cabezas, Susan P. Conner, Satarupa Dasgupta, Mfon Umoren Ekpootu, Raelene Frances, Pamela Fuentes, Sue Gronewold, Hanan Hammad, Shawna Herzog, Philippa Hetherington, Nicole Keusch, Liat Kozma, Julia Laite, Nomi Levenkron, Mary Linehan, Maja Mechant, Fernanda Nuñez, Marion Pluskota, Cristiana Schettini, Hila Shamir, Yvonne Svanström, Isabelle Tracol-Huynh, Michela Turno, Elise van Nederveen Meerkerk, and Mark David Wyers.